CHARAKTER PRAWNY UZNANIA DZIECKA - Haberko, Joanna (Wydział Prawa i Administracji UAM, 1999)
The paper relates to legal character of fathering a child by his natural father. This act is a typical act in the law. It is a personal action of the acting subject though for its effectiveness a consent of some persons defined by the law is needed. A declaration deposited does confirm the existing state of facts which is an effect of previously occured events. Factual state acquires in the act of fathering its legal convalidness and subjects of such a legal relationship do acquire rights and obligations. One can not deny that an act of fathering a child has a quality of legal action which contains as well a declaration of will as, in the same time, a statement of knowledge. This act is determined by the legislator in provisions of the family and guardianship code, however it is not in full conformity with the acts as defined within the civil code. Such a solution is nevertheless the effect of conscient standpoint of the legislator who resigns good solutions comprised in civil code (and concerning general civil relationships) for the benefit of better solutions which do more adequately meet family relations.
LEGAL CHARACTER OF FATHERING A CHILD